Report of the Secretary-General on the Work of the Organization 2019 - United Nations (United Nations, 2019)
This report reflects upon the challenges and opportunities the United Nations has faced over the past year. It presents an account of the progress made and the impact of the work of the Organization across its priorities of maintaining international peace and security, protecting human rights, delivering humanitarian aid, promoting sustainable development and upholding international law. It offers a frank, realistic analysis of current global issues and emphasizes the importance of multilateral action to maintain and improve the current world situation.